ТЕХНОЛОГИЯ БАҒДАРЫНДА ЭЛЕКТРОТЕХНИКАЛЫҚ ПӘНЛЕРДИ ОҚЫТЫЎДА ЖАСЛАРДЫҢ ДӨРЕТИЎШИЛИК ҚӘБИЛЕТИН РАЎАЖЛАНДЫРЫЎ УСЫЛЛАРЫ - Әширбекова, С.У.; Кдырниязова, К.Р. (SCIENCE and SOCIETY, 2021)
This article discusses the peculicirity of teaching electrical engineering to students of the speciality of technology and studied the methodology of teaching electrical engeneering, provides technologies and the basics of teaching. The importance of using and teaching technology is shown on the study of electrical engineering.